A Novel Approach to Optimize Vitamin D Intake in Belgium through Fortification Based on Representative Food Consumption Data. Issue 10 (17th June 2019) - Moyersoen, Isabelle; Devleesschauwer, Brecht; Dekkers, Arnold; Verkaik-Kloosterman, Janneke; De Ridder, Karin; Vandevijvere, Stefanie; Tafforeau, Jean; Van Oyen, Herman; Lachat, Carl; Van Camp, John
ABSTRACT: Background: Food fortification is a promising means to improve vitamin D intake of a population. Careful selection of food vehicles is needed to ensure that nearly all individuals within the population benefit from the fortification program. Objectives: The aim of the study was to develop and apply a model that simultaneously selects the optimal combination of food vehicles and defines the optimal fortification level that adequately increases vitamin D intake in the population without compromising safety. Methods: Food consumption data from the Belgian Food Consumption Survey 2014 ( n =  3200; age 3–64 y) were used. The optimization model included 63 combinations of 6 potential vehicles for food fortification, namely "bread, " "breakfast cereals, " "fats and oils, " "fruit juices, " "milk and milk beverages, " and "yogurt and cream cheese." The optimization procedure was designed to minimize inadequate or excessive vitamin D intake in each of the food combinations. This allowed the relative ranking of the different combinations according to their fortification utility. The estimated average requirement and upper intake level were used as thresholds. An age-specific and population-based approach enabled the sensitivity of the population subgroups to adverse health effects to be taken into account. Feasibility, technical aspects, and healthiness of the food vehicles were used to select the optimal combination. Results: Multiple combinations of food vehicles significantly reduced the prevalence of inadequate vitamin D intake within the Belgian population (from 92–96% to <2%). Taking other aforementioned criteria into account, the fortification of "milk and milk beverages" and "bread" with 6.9 μg vitamin D/100 kcal was proposed as an optimal fortification scenario. Conclusions: The optimization model allows identification of an effective fortification scenario to improve vitamin D intake within the Belgian population based on acceptable risks of inadequate and excessive intake. The model can be extended to other micronutrients and other populations.